Development of Teaching Materials for Writing Skill Using PowerPoint at Islamic High School - Afifah, Nor (Nurul Jadid University, 2024)
Writing skill has become very important in the field of foreign language education. Based on the results of the preliminary study, it appears that the interest of Al-Shifa High School in teaching students to write in Arabic is still low due to the teacher's lack of creativity in using media other than the blackboard and little practice. Therefore, their writing proficiency is weak. From observation, the researcher found that the school has a projector (LCD). Therefore, the researcher developed teaching materials using PowerPoint. The objectives of this research are: 1). To know the development of teaching materials using PowerPoint to improve writing skills at Al-Shifa Islamic High School, Central Sulawesi, 2). To know the effectiveness of developing teaching materials using PowerPoint to improve writing skills at Al-Shifa Islamic High School, Central Sulawesi. This research used the Research And Development approach and the Borg and Gall method. The research approach used in this research is qualitative and quantitative. Data collection method is through observation, interview, questionnaire, and test. Then the data collected is analyzed using the Product Moment correlation formula with the help of SPSS. The results of this research are: 1) The method of developing educational materials using PowerPoint is as follows: needs analysis, information collection, production design, production validation, production improvement, field experiment, second production improvement, and final production. 2) The effectiveness of developing educational materials for writing skill using PowerPoint is effective because it depends on the data obtained by the researcher in the form of evaluation tests and questionnaires. There are phenomena of effectiveness in the test results that the average of the pre-test results is 64% and the average of the post-test results is 78.4%.